Remote constraint induced therapy of the upper extremity (ReCITE): A feasibility study protocol - Christie, Lauren J.; Fearn, Nicola; McCluskey, Annie; Lannin, Natasha A.; Shiner, Christine T.; Kilkenny, Anna; Boydell, Jessamy; Meharg, Annie; Howes, Ella; Churilov, Leonid; Faux, Steven; Doussoulin, Arlette; et al. (Frontiers in Neurology, 2022)
Background: Difficulty using the upper limb in everyday activities is common after stroke. Constraint-induced movement therapy (CIMT) has been shown to be effective in both sub-acute and chronic phases of stroke recovery and is recommended in clinical practice guidelines for stroke internationally. Despite reports of equivalence of outcome when stroke rehabilitation interventions are delivered using telehealth, there has been limited evaluation of CIMT when using this mode of delivery. ReCITE will a) evaluate the feasibility and acceptability of CIMT when delivered via telehealth to stroke survivors (TeleCIMT) and b) explore therapists' experiences and use of an online support package inclusive of training, mentoring and resources to support TeleCIMT delivery in clinical practice. Methods: A prospective single-group, single blinded, study design with embedded process evaluation will be conducted. The trial will be conducted at three outpatient services in Sydney, Australia. A multi-faceted therapist support package, informed by the Capabilities, Opportunity, Motivation- Behaviour model (COM-B), will be used to support occupational therapists to implement TeleCIMT as part of routine care to stroke survivors. Each service will recruit 10 stroke survivor participants (n=30) with mild to moderate upper extremity impairment. Upper extremity and quality of life outcomes of stroke survivor participants will be collected at baseline, post-intervention and at a four-week follow-up. Feasibility of TeleCIMT will be evaluated by assessing the number of stroke participants who complete 80% of intensive arm practice prescribed during their three week program (i.e. at least 24 hours of intensive arm practice). Acceptability will be investigated through qualitative interviews and surveys with stroke survivors, supporter surveys and therapist focus groups. The qualitative interviews with therapists will provide additional data to explore their experiences and use of the online support package. Discussion: The COVID-19 pandemic resulted in a rapid transition to delivering telehealth. The proposed study will investigate the feasibility and acceptability of delivering a complex intervention via telehealth to stroke survivors at home, and the support that therapists and patients require for delivery. The findings of the study will be used to inform whether a larger, randomised controlled trial is feasible.